Trgovska blagovna znamka - Pfajfar, Gregor (Teorija in praksa, 2007)
Successful global companies are aware of the fact that their brands represent the core value of an enterprise. Companies can build their business only through loyal customers by creating strong brand identity. Diverse products and services that can satisfy the same needs show the importance of brands, which represent unique identity to the customer. The result of this exceptional market circumstances is the phenomenon called store brands. Retailers are creating their own brands because they see brands as a way of store image improvement, increase of business profitability and acquirement of new satisfied customers. A brand can lead to such results if retailers develop well-structured strategy of brand introduction and plan ahead to what source expenditure it would arise. Only then it is possible for brand to deliver what is promised. The authors therefore present a theoretical framework including strategic business analysis of existent brands, construction of new brand identity system and finally directions, which lead to successful brand identity system implementation. Nevertheless, the retailers have to study consumer behaviour factors, which would lead target consumers to our store brand.
Keywords: corporation; podjetje; trženje; blagovne znamke; identiteta; pozicioniranje; nakup; odločanje